"Give me one but not the other": the substitution effects of supervisor's organizational status and salesperson internal networking on performance growth trajectories. Issue 1 (24th September 2020) - Lee, Na Young; Dugan, Riley; Rouziou, Maria; Anwar, Ali
Abstract: Despite recent attention from scholars, internal networking remains underexplored in the sales literature, particularly with respect to its effect on longitudinal measures of performance. The current research addresses this notable omission by examining the interactive effect of salespeople's internal networking ability and their supervisor's organizational status on performance growth trajectories. Utilizing 20 quarters of individual, financial performance data from 113 salespeople at a warehousing equipment manufacturer, we find that both internal networking and a supervisor's organizational status drive a salesperson's performance growth trajectory. However, the interaction of these two variables has a negative – and counterintuitive – effect on performance growth trajectory. That is, supervisors with high organizational status attenuate (buttress) the performance growth of their high (low) networking salespeople. Taken together, these results reveal an important boundary condition regarding the efficacy of internal networking, and underscore the importance of sales managers in shaping the effectiveness of their salespeople's internal networking efforts.